Variations in infant feeding practice are associated with body composition in childhood: a prospective cohort study. - Robinson, S; Marriott, L; Crozier, SR; Harvey, N; Gale, C; Inskip, H; Baird, J; Law, C; Godfrey, K; Cooper, C (2009)
CONTEXT: Most studies of infant diet and later body composition focus on milk feeding; few consider the influence of variations in the weaning diet. OBJECTIVE: Our objective was to examine how variations in milk feeding and the weaning diet relate to body composition at 4 yr. STUDY POPULATION: A total of 536 children participating in a prospective birth cohort study. DESIGN: Diet was assessed at 6 and 12 months of age. Compliance with weaning guidance was defined by the infant's score for a principal component analysis-defined dietary pattern (infant guidelines) at 12 months. Infants with high infant guidelines scores had diets characterized by high consumption of fruit, vegetables, and home-prepared foods. Body composition was assessed at 4 yr by dual x-ray absorptiometry. RESULTS: Longer duration of breastfeeding was associated with lower fat mass at 4 yr [4.5 kg, 95% confidence interval (CI) of 4.3-4.7 kg, in children breastfed for 12 months or more, compared with 5.0 (95% CI 4.7-5.3) kg in children never breastfed (P = 0.002)] but was not related to body mass index. Children with high infant guidelines scores had a higher lean mass [12.6 (95% CI 12.3-12.9) kg in children in the top quarter of the distribution, compared with 12.0 (95% CI 11.7-12.4) kg in children in the bottom quarter (P = 0.001)]. These associations were independent and were little changed by adjustment for confounding factors. CONCLUSIONS: These data suggest that variations in both milk feeding and in the weaning diet are linked to differences in growth and development, and they have independent influences on body composition in early childhood.